ENACT (ENvironmental enrichment for infants; parenting with Acceptance and Commitment Therapy): a randomised controlled trial of an innovative intervention for infants at risk of autism spectrum disorder - Koa Whittingham; Roslyn N Boyd; Andrea McGlade; Kavindri Kulasinghe; Amy E Mitchell; Honey Heussler (BMJ Open)
Introduction Autism spectrum disorder (ASD) is a heterogeneous neurodevelopmental condition with impacts on behaviour, cognition, communication, social interaction and family mental health. This paper reports the protocol of a randomised controlled trial (RCT) of a very early intervention, ENACT (ENvironmental enrichment for infants; parenting with Acceptance and Commitment Therapy), for families of infants at risk of ASD.Methods and analysis We aim to recruit 66 mothers of infants at risk of ASD (ie, infants with a sibling or parent diagnosed with ASD) to this RCT. Families will be randomly assigned to care-as-usual or ENACT. ENACT is a very early intervention, leveraging parent–child interactions to improve early social reciprocity, while supporting parental mental health and the parent–child relationship through Acceptance and Commitment Therapy. Intervention content is delivered online (approximately 8 hours) and supported by more than 7 consultations with a clinician. Parents will perform the social reciprocity intervention with their child (30 min per day). Assessments at four time points (baseline, 3 months, 6 months, and 12 months corrected age) will assess parent–infant interaction, parental mental health, infant development and early ASD markers. Analysis will be by intention to treat using general linear models for RCTs.Ethics and dissemination This protocol has been approved by the Children’s Health Queensland Hospital and Health Service Human Research Ethics Committee (HREC/19/QCHQ/50131) and the University of Queensland Human Research Ethics Committee (2019000558). If efficacy is demonstrated, the intervention has the potential for wide and accessible dissemination.Trial registration number Australian New Zealand Clinical Trials Registry (ACTRN12618002046280).